Analysis of manganese nodules of the Scripps collection - Jane Z Frazer; Mary B Fisk (PANGAEA, 1976)
The Marine Minerals Database contains geochemical analyses and auxiliary information on present-day marine deposits of primarily ferromanganese nodules and crusts. Some data for heavy minerals are also included. Sources of ferromanganese analyses include the historic Scripps Institution of Oceanography (SIO) manganese nodule analysis file compiled under the direction of Jane Frazer and Mary Fisk.